Realistic Vision in Aristotle's Moral Philosophy - Humaidi, Sabah (Al-Adab Journal, 2025)
Aristotle's realistic vision in ethics was not far from the reality of Greek society with all its traditions and beliefs; in addition to this reality, it did not neglect the external and lived reality; the ethical research of Aristotle was looking into the moral virtues according to this realistic vision.Aristotle's main meaning of virtue is the complete readiness and execution of an action; it is the moral quality that makes a man a good man when he performs his own work to the fullest.Aristotle divides virtue into two parts: The first, mental, is natural, produced and developed by education and needs experience and time; the second, moral, is acquired, produced and generated by habit and character. Moral virtue is a state of natural and rational balance between excess and excess.In this research, we tried to clarify the moral purpose of the early Greek philosophers, from Socrates and Plato to Aristotle, and discussed the main differences in the interpretation of virtues between Socrates and Plato's vision and Aristotle's vision, in addition to Aristotle's realistic vision of practical moral virtues and theoretical mental virtues, such as goodness, justice and courage, in addition to Aristotle's realistic vision in practical moral virtues and theoretical mental virtues.